Pedagogical Scaffolding and Cohesive Writing in English First Additional Language Classroom: The Qualitative Case Study of Grade 9 Teaching Practices in Rural Secondary School - Motlhaka, Hlaviso; Sebone, Mamoshaba (Universitas Jambi, Magister Program of English Education Department, 2026)
This study examined the pedagogical practices employed in teaching essay writing to Grade 9 English First Additional Language (EFAL) learners in a rural Limpopo school, analysing the relationship between these practices and learners' use of cohesive devices in written composition. Drawing on non-participant observations of six one-hour lessons, semi-structured interviews with two EFAL teachers, and systematic document analysis of 10 learner essays using a cohesive devices analytical framework, the study investigated how instructional approaches shape learners' capacity to produce coherent, cohesive texts. The findings indicate that both observed teachers predominantly employed teacher-centred, product-oriented approaches that emphasised grammatical accuracy and structural replication over the recursive processes of planning, drafting, and revising. Analysis of learner essays revealed limited use of cohesive devices, with deficits in conjunctive adverbs, lexical cohesion through synonymy, and referential clarity. The study establishes empirical connections between specific instructional practices particularly the absence of explicit modelling of cohesive ties, insufficient formative feedback on discourse-level organisation, and decontextualised grammar instruction, and the cohesive deficits evident in learner writing. Therefore, this study concludes with recommendations for targeted professional development in discourse-oriented writing pedagogy and the establishment of professional learning communities focused on cohesive writing instruction.